Recommendations for bean production in Malawi - National Bean Programme (National Bean Programme, 1990)
Aspects regarding the importance of beans in Malawi are discussed as well as uses, and types (based on growth habit and uses). Recommendations are given for bean cultivation under rainfed, residual moisture (irrigation schemes), and irrigated conditions regarding land preparation; var.; seed rate; planting time; fertilizers; plant population and spacing; disease, pest, and weed control; shelling; storage; intercropping with maize or in rotation with tobacco; seed quality, and water management. (CIAT)